The success rate of immediate implant placement of mandibular molars: A clinical and radiographic retrospective evaluation between 2 and 8 years - Hayacibara, Roberto M.; Gonçalves, Camila S.; Garcez-Filho, João; Magro Filho, Osvaldo [UNESP]; Esper, Helen; Hayacibara, Mitsue F. (Wiley, 2013)
Background: Dental implants, indicated for re-establishing both mastigatory and aesthetic functions, can be placed in the sockets immediately after tooth extraction. Most studies investigate the anterior and upper regions of the dental arch, whereas few examine longitudinal appraisal of immediate implant installation in the mandibular molar region. Objective: The aim of this retrospective study was to evaluate the success rate of immediate dental implants placement in mandibular molars within a follow-up period as long as 8 years. Materials and methods: Seventy-four mandibular molar implants after non-traumatic tooth extraction between 2002 and 2008 were examined in the study. All implants were evaluated radiographically immediately after prosthesis placement, 1 year after implantation, and by the end of the experimental period, in 2010. Clinical evaluation was done according to [Albrektsson et al. (1986) The International Journal of Oral & Maxillofacial Implants, 1, 11-25] success criteria for marginal bone loss. The mean bone losses, calculated as the difference between the final evaluation measures and those taken by the end of the first year of implant, were compared using Kruskal-Wallis test with a significance level of 5%. Results: All implants presented clinical and radiographic stable conditions, that is, 100% success rate. Significant bone loss was not found between final evaluation and that of the first functional year (P > 0.05). Conclusion: Immediate implant placement of mandibular molars proved to be a viable surgical treatment given the high success rate up to 8 years after implantation. © 2012 John Wiley & Sons A/S.
Keywords: Extensive follow-up; Extraction socket; Immediate implant; Mandibular molars; Osseointegration